2011
DOI: 10.1590/s0004-282x2011000300018
|View full text |Cite
|
Sign up to set email alerts
|

Lipoic acid effects on glutamate and taurine concentrations in rat hippocampus after pilocarpine-induced seizures

Abstract: Pilocarpine-induced seizures can be mediated by increases in oxidative stress and by cerebral amino acid changes. The present research suggests that antioxidant compounds may afford some level of neuroprotection against the neurotoxicity of seizures in cellular level. The objective of the present study was to evaluate the lipoic acid (LA) effects in glutamate and taurine contents in rat hippocampus after pilocarpine-induced seizures. Wistar rats were treated intraperitoneally (i.p.) with 0.9% saline (Control),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 27 publications
2
6
0
Order By: Relevance
“…Several reports demonstrated that LPO levels and nitrite content in the brain of adult rats were increased after the acute phase of seizures induced by pilocarpine [ 113 115 ]. Agreeing with these results other works have shown in rat hippocampus a significant increase in CAT activity, glutamate content, and a decrease in taurine level [ 116 ], as well as the increase of ROS generation in CA1, CA3, and the dentate gyrus [ 117 ]. The reduction of the functions of these systems during SE produced by Pilocarpine suggests an involvement of oxidative stress in neuronal death in this experimental epilepsy model.…”
Section: Experimental Modelssupporting
confidence: 75%
“…Several reports demonstrated that LPO levels and nitrite content in the brain of adult rats were increased after the acute phase of seizures induced by pilocarpine [ 113 115 ]. Agreeing with these results other works have shown in rat hippocampus a significant increase in CAT activity, glutamate content, and a decrease in taurine level [ 116 ], as well as the increase of ROS generation in CA1, CA3, and the dentate gyrus [ 117 ]. The reduction of the functions of these systems during SE produced by Pilocarpine suggests an involvement of oxidative stress in neuronal death in this experimental epilepsy model.…”
Section: Experimental Modelssupporting
confidence: 75%
“…In line with this finding, previous studies have shown that in the acute phase of epilepsy, glutamate levels in the hippocampal tissue increase significantly [48]. This increase is likely due to the increased production of glutamate from glucose in the citric acid cycle (TCA) following the severe need for neurons after continuous stimulations.…”
Section: Discussionsupporting
confidence: 65%
“…a-Lipoic acid can respond to oxidative stressinduced apoptosis and improve the cell viability. 1,19 As studies have demonstrated, a promising candidate solution to protect the brain from neurons damage is linked with the activity of anti-oxidant enzymes.…”
Section: Introductionmentioning
confidence: 99%